2008
DOI: 10.1111/j.1349-7006.2008.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length and the risk of lung cancer

Abstract: Telomeres play a key role in the maintenance of chromosome integrity and stability. There is growing evidence that short telomeres induce chromosome instability and thereby promote the development of cancer. We investigated the association of telomere length and the risk of lung cancer. Relative telomere length in peripheral blood lymphocytes was measured by quantitative polymerase chain reaction in 243 lung cancer patients and 243 healthy controls that were frequency-matched for age, sex and smoking status. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
153
6
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(175 citation statements)
references
References 43 publications
9
153
6
1
Order By: Relevance
“…The associations generally remained after adjustment for age and are probably fairly robust as the chromosomal aberrations scoring has been validated (Savage, 1976;Brøgger et al, 1990) and the telomere length and the LINE1 methylation analyses demonstrated low coefficients of variation (Jang et al, 2008; Mumford et al, 2008;Shen et al, 2009;Hossain et al, 2012). The finding of more LINE1 methylation with higher frequency of chromosomal aberrations was in contrast to expected.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The associations generally remained after adjustment for age and are probably fairly robust as the chromosomal aberrations scoring has been validated (Savage, 1976;Brøgger et al, 1990) and the telomere length and the LINE1 methylation analyses demonstrated low coefficients of variation (Jang et al, 2008; Mumford et al, 2008;Shen et al, 2009;Hossain et al, 2012). The finding of more LINE1 methylation with higher frequency of chromosomal aberrations was in contrast to expected.…”
Section: Discussioncontrasting
confidence: 50%
“…Telomeres are of great importance in maintaining chromosomal stability and cellular DNA damage and repair (Hahn, 2003;Callen and Surralles, 2004;Blasco, 2005;Rodier et al, 2005). Short average telomere length in peripheral blood appears to be a susceptibility marker for human breast, bladder, head and neck, lung, and renal cell cancers (Wu et al, 2003;Broberg et al, 2005;Shen et al, 2007;Jang et al, 2008) and meta studies show that the presence of shortened telomeres is a marker for susceptibility to human cancer, but for which cancer types is not clearly established Wentzensen et al, 2011). Short telomere length caused chromosomal instability and epithelial carcinogenesis in mice (Artandi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found evidence of heterogeneous effects according to cancer type, whereby tumors with a high fatality rate tended to exhibit more prominent relationships with telomere length and tumors with a more favorable prognosis showed modest or no associations. These results corroborate with previous evaluations demonstrating a link between short telomere length and lung cancer, bladder cancer, renal cell carcinoma, non-Hodgkin lymphoma and head and neck tumors (Wu, Amos et al 2003;Broberg, Bjork et al 2005;McGrath, Wong et al 2007;Shao, Wood et al 2007;Jang, Choi et al 2008;Lan, Cawthon et al 2009), but failed to obtain significant correlations between short telomere length and colorectal and breast cancer (De Vivo, Prescott et al 2009;Shen, Gammon et al 2009;Zee, Castonguay et al 2009). A variety of experimental and genetic studies support the hypothesis that telomere attrition contributes to the manifestation and dissemination of malignancies.…”
Section: Blood Telomere Length As a Potential Predictor For Cancer Risupporting
confidence: 81%
“…However, previous reports from this research area are not unambiguous. In renal, lung, bladder, head and neck and oesophagus carcinomas, short TL in peripheral blood have been associated with increased cancer risk (Wu, Amos et al 2003;McGrath, Wong et al 2007;Risques, Vaughan et al 2007;Jang, Choi et al 2008). Similar data have been reported for malignant lymphoma (Widmann, Herrmann et al 2007).…”
Section: Blood Telomere Length As a Potential Predictor For Cancer Risupporting
confidence: 73%
“…In recent years, several epidemiological studies (case-control and/or cohort) have reported on the association between TL and a number of cancers such as lung, 7,8 breast, [9][10][11] bladder, 12,13 renal, 14,15 gastric, 16,17 esophageal, 18,19 colorectal, 20,21 and lymphomas. 22,23 Interestingly, according to the most recent meta-analysis on TL and cancer, reported results of What's new?…”
mentioning
confidence: 99%